Overview: Systemic Inflammatory Response Derived From Lung Injury Caused by SARS-CoV-2 Infection Explains Severe Outcomes in COVID-19 - Polidoro, Rafael B.; Hagan, Robert S.; de Santis Santiago, Roberta; Schmidt, Nathan W. (Frontiers in Immunology, 2020)
Most SARS-CoV2 infections will not develop into severe COVID-19. However, in some patients, lung infection leads to the activation of alveolar macrophages and lung epithelial cells that will release proinflammatory cytokines. IL-6, TNF and IL-1β increase expression of cell adhesion molecules (CAMs) and VEGF, thereby increasing permeability of the lung endothelium and reducing barrier protection, allowing viral dissemination and infiltration of neutrophils and inflammatory monocytes. In the blood, these cytokines will stimulate the bone marrow to produce and release immature granulocytes, that return to the lung and further increase inflammation, leading to acute respiratory distress syndrome (ARDS). This lung-systemic loop leads to cytokine release syndrome (CRS). Concurrently, the acute phase response increases the production of platelets, fibrinogen and other pro-thrombotic factors. Systemic decrease in ACE2 function impacts the Renin-Angiotensin-Kallikrein-Kinin systems (RAS-KKS) increasing clotting. The combination of acute lung injury with RAS-KKS unbalance is herein called COVID-19 Associated Lung Injury (CALI). This conservative two-hit model of systemic inflammation due to the lung injury allows new intervention windows and is more consistent with the current knowledge.